Chemical Composition, Health Benefits and Applications of Chia seeds: A Review - Shrestha, Megha; Shrestha, Salina; Shrestha, Nabindra Kumar (Tribhuvan University Journal of Food Science and Technology, 2022)
Consumers have adjusted their dietary preferences toward better food options as public health awareness has grown, and demand for functional food with many health advantages has increased. Chia, a plant native to Mexico and Guatemala, is commonly consumed for its health advantages related to chronic disorders like obesity, diabetes, and cancer. The high content of essential fatty acids, fibre, and antioxidants in this food contributes to its health benefits. It can be eaten on its own or mixed into yoghurt, salads, fruits, pastries, and beverages. Chia seeds have both a preventative and therapeutic effect on health, since their antioxidant capabilities protect the cardiovascular system from disease, while unsaturated omega-3 fatty acids assist lower serum cholesterol levels. Chia seed gum can be used as an alternative in food as an emulsifier, additive and foam stabilizer. Therefore, it is considered as a superfood.